2019
DOI: 10.1016/j.jobe.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Personal CO2 bubble: Context-dependent variations and wearable sensors usability

Abstract: High CO2 concentration in inhaled air has been shown to negatively impact work performance and increase acute health symptoms. As respiratory CO2 is constantly exhaled, it may not dissipate in surrounding air in absence of adequate air movement and is instead re-inhaled into the airways (breathing in a CO2-rich bubble). In this study, we explored the impacts of context-dependent factors such as office activities, desk settings, and personal differences on the inhalation zone CO2 concentration and on concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The manikin was exposed to higher CO2 concentration than the concentration at the exhaust. These results concurred with the recently reported results [18]. In [18] the elevated CO2 concentration in the inhaled air is attributed to the personal CO2 bubble generated in the breathing zone due to the exhaled air, i.e.…”
Section: Resultssupporting
confidence: 93%
“…The manikin was exposed to higher CO2 concentration than the concentration at the exhaust. These results concurred with the recently reported results [18]. In [18] the elevated CO2 concentration in the inhaled air is attributed to the personal CO2 bubble generated in the breathing zone due to the exhaled air, i.e.…”
Section: Resultssupporting
confidence: 93%
“…The air movement offsets the need for air cooling by increasing the convective cooling of the occupants' bodies. It has also been found that a modest air speed significantly reduces a CO2 bubble that accumulates in a person's breathing zone under still air conditions in workstations [16]. Finally, higher air temperatures and air speeds have also recently been shown to be far more effective (compared to cooler temperatures and still-air) at restoring comfort to occupants who have just entered a space with elevated metabolic rate and stored body heat from walking [17,18].…”
Section: Comfort Zones and Air Quality Effects Under Elevated Air Movmentioning
confidence: 99%
“…CO 2 concentrations exceeding 950 ppm were found to cause significant declines in cognitive scores, even though the level of exposure is considered acceptable by ASHRAE 62.1, which provides ventilation guidelines for acceptable indoor air quality (Allen et al, 2016). Past studies have shown that the exhaled CO 2 does not immediately dissipate with the surrounding air when occupants are sedentary and results in a buildup of a personal CO 2 bubble around the occupant's head (Ozkaynak et al, 1996;Ghahramani et al, 2019). A recent study has shown that using a desk fan can dissipate the CO 2 bubble and reduce the CO 2 concentration by 177 ppm on average (Ghahramani et al, 2019).…”
Section: Air Qualitymentioning
confidence: 99%
“…Past studies have shown that the exhaled CO 2 does not immediately dissipate with the surrounding air when occupants are sedentary and results in a buildup of a personal CO 2 bubble around the occupant's head (Ozkaynak et al, 1996;Ghahramani et al, 2019). A recent study has shown that using a desk fan can dissipate the CO 2 bubble and reduce the CO 2 concentration by 177 ppm on average (Ghahramani et al, 2019). The use of personal fans can maintain comfortable thermal conditions while also reducing CO 2 concentration and improving perceived air quality even when the air movement is from recirculated room air (Zhang et al, 2010;Ghahramani et al, 2019).…”
Section: Air Qualitymentioning
confidence: 99%
See 1 more Smart Citation